Evaluation of Carboxymethyl Cellulose (CMC) Binder and Squid Oil Attractant in the Formulation of Litopenaeus vannamei Diet - Nor Asma Husna Yusoff; Mohd Ihwan Zakariah; Jalilah Mohamad; Sharifah Rahmah; Marina Hassan (Jurnal Ilmiah Perikanan dan Kelautan, 2021)
Highlight ResearchEffects of carboxymethyl cellulose (CMC) binder on pellet water stability in shrimp diet.Evaluation of squid oil attractant on feed palatability.The quality of water after inclusion of CMC binder and squid oil in pellet.CMC and squid oil improved dry matter retention and feeding responses in shrimp. AbstractPellet water stability and feeding attractant are the crucial factors to be considered in the formulation of shrimp feed to minimize nutrient leaching and improve food palatability, respectively. The aim of this study was to determine the binding effect of supplementation of carboxymethyl cellulose (CMC) during pellet manufacturing, and feeding responses with the inclusion of squid oil in pellet. Both experiments were conducted separately in five feed formulations ranged from 0.00% to 3.00% of CMC and squid oil. All T0 was referred as control with no CMC or squid oil. Experiment was conducted using 30 shrimps/treatment with triplicates. The dry matter retention up to 120 min of immersion and the feeding response test were evaluated in pellet supplemented with CMC and squid oil, respectively. Results showed the percentage of dry matter retentions increased with the increase of CMC, over time. The CMC containing pellets at 2.00% and 3.00% had minimal disintegration in water and possessed high water stability after 120 min immersion. The addition of 3.00% squid oil in feed exhibited a significant result (p<0.05) in the time taken for shrimp to access the pellet, also increased the time starts for ingestion. No significant change was observed in water quality indicated no water contamination occurred throughout the study. Results demonstrated that the addition of CMC binder at 2.00% and 3.00% improved pellet water stability, whilst 3.00% squid oil was recommended to enhance feed palatability. However, future studies on the activity of enzymes in shrimp bodies after treatment would be an advantage.